Mamdani fuzzy-based vehicular grouping at the intersection of roads for smart transportation system. (5th April 2019) - Maddiboyina, Harsha Vardan; Ponnapalli, V.A. Sankar
Smart transportation system is an innovative solution to the traffic congestion at the real-time traffic environment. A smart transportation system based on vehicular grouping technique with length as a parameter has proposed in this research contribution to avoid traffic congestion at the intersection of roads. In this method, vehicles which are waiting at the intersection of roads are divided into small groups with highest priority given to the emergency vehicles. Owing to the proposed work, the average number of vehicles which can cross the junction is increased to 2.4 times compare with existing traffic statistics of Hyderabad City, India. Therefore the average waiting time of an emergency vehicle is diminished up to 38%. Mamdani fuzzy inference system has used to frame the fuzzy IF-THEN rules and MATLAB 2014a has used to simulate the proposed work.